2001
DOI: 10.1029/2001jb000178
|View full text |Cite
|
Sign up to set email alerts
|

Crustal thickness of the Peninsular Ranges and Gulf Extensional Province in the Californias

Abstract: Abstract. We estimate crustal thickness along an east-west transect of the Baja California peninsula and Gulf of California, Mdxico, and investigate its relationship to surface elevation and crustal extension. We derive Moho depth estimates from P-to-S converted phases identified on teleseismic recordings at 11 temporary broadband seismic stations deployed at -31øN latitude. Depth to the Moho is -33 ( In sections 2-4, we review the geologic setting for the study, describe the station deployment and data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
90
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 33 publications
17
90
1
Order By: Relevance
“…Furthermore, shear stress in the uppermost lower crust beneath San Quintín is similar to the shear strength of the San Andreas fault (10-17 MPa) in the upper crust, constrained from frictional properties of the San Andreas Fault Observatory at Depth core samples (Lockner et al, 2011;Carpenter et al, 2012) (Fig. 13a).…”
Section: Strength Of a Strike-slip Plate Boundarymentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, shear stress in the uppermost lower crust beneath San Quintín is similar to the shear strength of the San Andreas fault (10-17 MPa) in the upper crust, constrained from frictional properties of the San Andreas Fault Observatory at Depth core samples (Lockner et al, 2011;Carpenter et al, 2012) (Fig. 13a).…”
Section: Strength Of a Strike-slip Plate Boundarymentioning
confidence: 84%
“…The mafic composition of the western Peninsular Ranges batholith produces magnetic anomalies and seismic velocity contrast, which can be traced down to at least 20 km depth (Langenheim and Jachens, 2003). The crustal thickness increases from 21 to 26 km along the eastern Baja California peninsula to 29-38 km below the western Peninsular Ranges batholith (Lewis et al, 2001;Paulssen and De Vos, 2017).…”
Section: Geology Of the Baja California Microplatementioning
confidence: 99%
“…Others have argued that uplift of the same terraces results from large-scale tectonic processes such as flexural response to rifting that are largely independent of motion on individual faults (Muhs et al, 1992;Orme, 1998;Kier et al, 2001). Geophysical data and modeling show that high topography in the Peninsular Ranges is presently supported by thinning of mantle lithosphere related to extension in the Salton Trough and Gulf of California (Lewis et al, 2000(Lewis et al, , 2001, but this mechanical model does not provide any constraint on the timing of regional uplift. Thus, the timing and rate of Cenozoic uplift in the Peninsular Ranges, and possible links to coastal deformation, remain poorly known.…”
Section: Evolution Of Regional Topographymentioning
confidence: 96%
“…5a) under Mexicali Valley and Laguna Salada, is a regional feature; however, there is little to no change in the topography. A receiver function study by Lewis et al (2001), done ∼140 km south of our study area, suggested that the change in the Moho depth, from west to ▴ Figure 6. Comparison of the previous crustal and upper-mantle velocity models for the Mexicali Valley (MVM and C11M) against our new model for the southern Mexicali Valley (SMVM).…”
Section: Discussion Velocity Structure Modelmentioning
confidence: 99%